Combination of Secondary Plant Metabolites and Micronutrients Improves Mitochondrial Function in a Cell Model of Early Alzheimer’s Disease - Babylon, Lukas; Meißner, Julia; Eckert, Gunter P.; Justus Liebig University Giessen (My University, 2023)
Alzheimer’s disease (AD) is characterized by excessive formation of beta-amyloid peptides (Aβ), mitochondrial dysfunction, enhanced production of reactive oxygen species (ROS), and altered glycolysis. Since the disease is currently not curable, preventive and supportive approaches are in the focus of science. Based on studies of promising single substances, the present study used a mixture (cocktail, SC) of compounds consisting of hesperetin (HstP), magnesium-orotate (MgOr), and folic acid (Fol), as well as the combination (KCC) of caffeine (Cof), kahweol (KW) and cafestol (CF). For all compounds, we showed positive results in SH-SY5Y-APP695 cells—a model of early AD. Thus, SH-SY5Y-APP695 cells were incubated with SC and the activity of the mitochondrial respiration chain complexes were measured, as well as levels of ATP, Aβ, ROS, lactate and pyruvate. Incubation of SH-SY5Y-APP695 cells with SC significantly increased the endogenous respiration of mitochondria and ATP levels, while Aβ1–40 levels were significantly decreased. Incubation with SC showed no significant effects on oxidative stress and glycolysis. In summary, this combination of compounds with proven effects on mitochondrial parameters has the potential to improve mitochondrial dysfunction in a cellular model of AD.
Keywords: hesperetin; magnesium-orotate; folic acid; caffeine; kahweol; cafestol; ROS; Alzheimer’s disease; mitochondrial dysfunction; amyloid-beta; ddc:640; ddc:360